REFORMULATION OF REGIONAL REGULATIONS CONCERNING IMPLEMENTATION OF ISLAMIC BOARDING SCHOOLS IN PAREPARE CITY - Hasim, Hasanuddin; Mutmainnah, Iin (Institut Agama Islam Negeri Bone, 2023)
The effectiveness level of Law Number 18 of 2019 concerning Islamic Boarding Schools has actually been implemented quite well, but in the other case there are still several Islamic boarding schools that have inadequate facilities and infrastructure, especially in the Parepare city. Due to the fact that Islamic boarding schools are independent institutions so that the small amount of funds allocated is unable to provide adequate facilities and infrastructure. One of the government's efforts to carry out the mandate of Law Number 18 of 2019 regarding Islamic Boarding Schools is by issuing Presidential Regulation Number 82 of 2021 concerning Funding for the Implementation of Islamic Boarding Schools, in article 4 letter E and article 23 paragraph (1) provide for establishing endowment funds as funding for organizing Islamic boarding schools to ensure the continuity of educational programs in Islamic boarding schools. However, despite this, to perfect and achieve the effectiveness level of Law Number 18 of 2019 concerning Islamic Boarding Schools, derivative regulations are still needed to further explain the facilities for organizing Islamic boarding schools and reformulate this Law through Regional Regulations (Perda).